Association of chain of survival factors with out of hospital cardiac arrest survival in a region with low average population-density: a retrospective population-based cohort study. (25th November 2020) - Connolly, M; Goldstein, J; Giddens, K; Nallbani, M; Kennedy, P; Currie, M; Carter, A; Travers, A; Sapp, J
Abstract: Background: Out of hospital cardiac arrest (OHCA) has an average global survival rate to discharge of 8%. Chain of survival factors are heavily time-dependant and optimization can increase survival. Regions with low population density encounter challeges in providing optimal OHCA care. Nova Scotia's average population density is 17.4 persons per square kilometer in compasiron to Toronto with 4334.4 person per square kilometer. OHCAs have been described well in large urban centers globally, however the characterization of OHCA chain of survival in low density populations is sparse. Purpose: To describe chain of survival factors and identify characteristics of survivors and non-survivors among those treated by paramedics in a low average density provincial population. Methods: This was a retrospective cohort study of OHCAs responded to by paramedics. All OHCA responses with a cardiac etiology in Nova Scotia, Canada were included. Exclusion criteria were non-cardiac cause arrests, those with "do not resuscitate" (DNR) directives and expected deaths. The paramedic electronic patient care record was reviewed for demographic, bystander, out of hospital treatment and operational characteristics. Primary outcome was survival to hospital discharge. Descriptive statistics were calculated to describe differences between survivorship using Prism 8.0 (San Diego, CA) with alpha=0.05 applying unpaired, Mann-Whitney tests. Results: Of 1517 OHCA, 463 were excluded leaving 1054 OHCA. Of these, 478 (45.3%) were treated by paramedics and included in this analysis. Most were men (67.2%; n=274) with a mean age 66.8 (±16.4). A total of 7.1% (n=75) survived to discharge with 76% of survivors (n=58) discharged home. Survivors were more likely to present with ventricular fibrillation than non-survivors (42.7% vs. 19.6%). Survivors compared to non-survivors had significantly shorter paramedic response time (8.1 vs. 10.7 min, P<0.001), paramedic time on scene (35.7 vs. 45.4 min, P=0.002), estimated time to paramedic defibrillation (13.2 vs 19.4 min, P<0.001), and estimated time to return of spontaneous circulation (ROSC) (22.9 vs 31.9min, P<0.001). Conclusion: Links in the chain of survival are associated with survival from OHCA. OHCA survival is lower in the less densely populated province of Nova Scotia compared to studies in urban Canadian centers and worldwide. Our study is limited by the retrospective nature of data collection and lack of access to neurological outcomes. Even among survivors, EMS response is delayed compared to more densely populated centers. In Nova Scotia, longer paramedic response times are associated with decreased survival. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Maritime Heart Center